Synthesis, Characterization, and Electrocatalytic Properties of PrMn0.5M0.5O3 (M = Cr, Fe, Co, Ni) Perovskites - Cheliku Ramadani, Besarta; Sela, Jeta; Stojanov, Leon; Popovska, Sofija; Mircheski, Valentin; Bukleski, Miha; Dimitrovska-Lazova, Sandra; A. Reka; Arianit; Aleksovska, Slobotka (My University, 2025)
In this paper, the synthesis, characterization, and investigation of electrocatalytic properties of perovskites of general formula PrMn0.5M0.5O3 (M = Cr, Fe, Co, Ni) are presented. The synthesis was conducted by the solution combustion method using glycine as a fuel. The perovskite with the formula PrMn0.5Fe0.5O3 was also synthesized by the sol gel combustion method with citric acid as fuel. The obtained perovskites were investigated by X-ray powder diffraction (XRPD), scanning electron microscopy (SEM) with energy dispersive X-ray spectroscopy (EDX), infrared spectroscopy, and cyclic voltammetry. The XRPDpatterns showed that the compounds are pure and isostructural within the series. The unit cell parameters of the compounds were determined within the Pnma space group, and several crystallochemical parameters were calculated and discussed. The recorded SEM images of the perovskites revealed a porous morphology, while the EDX analysis confirmed the 2:1:1 atomic percentage ratio of Pr:Mn:M. Within this investigation, the electrocatalytic properties of the obtained perovskites towards oxidation of OH− ions and H2O2 oxidation in phosphate buffer were studied by cyclic voltammetry, using a paraffin impregnated graphite electrode (PIGE) modified with microcrystals of the investigated perovskites. PrMn0.5Fe0.5O3 showed high electrocatalytic activity for OH− oxidation, while both PrMn0.5Fe0.5O3 and PrMn0.5Co0.5O3 exhibited significant efficiency for H2O2 oxidation, with a distinct oxidation peak with a peak potential of 0.6 V.
Keywords: double manganese perovskites; XRPD; SEM; EDX; IR spectroscopy; cyclic voltammetry